2022
DOI: 10.7759/cureus.21101
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Cardiomyopathy and Atrial Fibrillation: A Review

Abstract: Hypertrophic cardiomyopathy (HCM) is an inherited cardiological condition that exhibits various clinical symptoms. The leading cause of atrial fibrillation (AF) in patients with HCM is advanced diastolic dysfunction and left atrial dilatation and remodeling. In addition to the gradual symptomatic and functional decline caused by AF, there is an increased risk of thromboembolic disease and mortality, especially if there is a rapid ventricular rate or obstruction of the left ventricular outflow tract. The mainst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In recent studies examining certain pathologies, inter-chamber differences and asymmetrical remodeling of the LA and RA could be demonstrated [20][21][22]. Several studies have shown that both atria are dilated, and their function deteriorates with arrhythmological consequences in the presence of certain cardiac diseases, even in children [23][24][25]. Moreover, dilation of the atria could also be detected in different pathologies and elite athletes, whose cardiac consequences were not widely known until recent times [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies examining certain pathologies, inter-chamber differences and asymmetrical remodeling of the LA and RA could be demonstrated [20][21][22]. Several studies have shown that both atria are dilated, and their function deteriorates with arrhythmological consequences in the presence of certain cardiac diseases, even in children [23][24][25]. Moreover, dilation of the atria could also be detected in different pathologies and elite athletes, whose cardiac consequences were not widely known until recent times [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertrophic cardiomyopathy (HCM) is a relatively common condition that can lead to SCD, even in young individuals, including well-trained athletes. This pathology affects both men and women, irrespective of their ethnicity [83].…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%